Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the quadratic equation [tex]\( x^2 + 3x - 54 = 0 \)[/tex] step-by-step.
### Step 1: Write down the quadratic equation
[tex]\[ x^2 + 3x - 54 = 0 \][/tex]
### Step 2: Identify the coefficients
The standard form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. From the given equation, we identify the coefficients:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 3 \)[/tex]
- [tex]\( c = -54 \)[/tex]
### Step 3: Calculate the discriminant
The discriminant [tex]\(\Delta\)[/tex] of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 3^2 - 4(1)(-54) \][/tex]
[tex]\[ \Delta = 9 + 216 \][/tex]
[tex]\[ \Delta = 225 \][/tex]
### Step 4: Determine the roots using the quadratic formula
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(\Delta\)[/tex] into the formula:
[tex]\[ x = \frac{-3 \pm \sqrt{225}}{2(1)} \][/tex]
[tex]\[ x = \frac{-3 \pm 15}{2} \][/tex]
### Step 5: Calculate the two possible solutions
1. For the positive square root:
[tex]\[ x = \frac{-3 + 15}{2} = \frac{12}{2} = 6 \][/tex]
2. For the negative square root:
[tex]\[ x = \frac{-3 - 15}{2} = \frac{-18}{2} = -9 \][/tex]
### Step 6: Write down the solutions
The solutions to the equation [tex]\( x^2 + 3x - 54 = 0 \)[/tex] are:
[tex]\[ x = -9 \quad \text{and} \quad x = 6 \][/tex]
So, the solutions are [tex]\( x = -9 \)[/tex] and [tex]\( x = 6 \)[/tex].
### Step 1: Write down the quadratic equation
[tex]\[ x^2 + 3x - 54 = 0 \][/tex]
### Step 2: Identify the coefficients
The standard form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. From the given equation, we identify the coefficients:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 3 \)[/tex]
- [tex]\( c = -54 \)[/tex]
### Step 3: Calculate the discriminant
The discriminant [tex]\(\Delta\)[/tex] of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 3^2 - 4(1)(-54) \][/tex]
[tex]\[ \Delta = 9 + 216 \][/tex]
[tex]\[ \Delta = 225 \][/tex]
### Step 4: Determine the roots using the quadratic formula
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(\Delta\)[/tex] into the formula:
[tex]\[ x = \frac{-3 \pm \sqrt{225}}{2(1)} \][/tex]
[tex]\[ x = \frac{-3 \pm 15}{2} \][/tex]
### Step 5: Calculate the two possible solutions
1. For the positive square root:
[tex]\[ x = \frac{-3 + 15}{2} = \frac{12}{2} = 6 \][/tex]
2. For the negative square root:
[tex]\[ x = \frac{-3 - 15}{2} = \frac{-18}{2} = -9 \][/tex]
### Step 6: Write down the solutions
The solutions to the equation [tex]\( x^2 + 3x - 54 = 0 \)[/tex] are:
[tex]\[ x = -9 \quad \text{and} \quad x = 6 \][/tex]
So, the solutions are [tex]\( x = -9 \)[/tex] and [tex]\( x = 6 \)[/tex].
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.